Development Of Adaptive Arabic Language Teaching Materials To Support Inclusive Learning - Hasim, Muhamad Fuad; Taufiq, Mirwan Akhmad; Ramadhani, Arya Pratama; Masitho, Dewi Nur; Nashirulloh, Adam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The increasing demand for inclusive education requires the availability of teaching materials that accommodate the diverse learning needs of all students, including those with special needs. As a subject with complex grammatical structures, Arabic presents a unique challenge in inclusive classroom settings, particularly in Islamic schools. This study examines the development of adaptive Arabic language teaching materials to support inclusive learning at MTs Miftahul Afkar Kediri. Using a qualitative approach with an evaluative-descriptive design, this research applies the CIPP (Context, Input, Process, Product) evaluation model, supported by the Universal Design for Learning (UDL) framework. Data were collected through classroom observations, in-depth interviews, and document analysis. The results show that Arabic teachers have independently developed adaptive teaching materials by simplifying content, using visual and audio supports, and adjusting learning activities to match the students’ varied needs. These efforts reflect UDL principles such as multiple means of representation and engagement, even though no training for teachers in UDL. Adaptive materials have positively impacted student motivation and participation, especially among students with learning barriers. Regular students also benefited from the more interactive and multimodal approach. However, several challenges remain, including institutional policy support, limited teacher training, and the lack of standardized material evaluation procedures. This study contributes to developing inclusive education practices in madrasahs by emphasizing the importance of adaptive teaching materials and the teacher’s role as a curriculum designer. The novelty of this study lies in its integration of the UDL approach within the context of Arabic instruction and the focus on student engagement as an indicator of effectiveness. Findings from this study offer a practical reference for other inclusive madrasahs seeking to develop equitable and accessible Arabic learning experiences for all students.